Tracking genomic cancer evolution for precision medicine: the lung TRACERx study. - Mariam Jamal-Hanjani; Alan Hackshaw; Yenting Ngai; Jacqueline Shaw; Caroline Dive; Sergio Quezada; Gary Middleton; Elza de Bruin; John Le Quesne; Seema Shafi; Mary Falzon; Stuart Horswell; et al. (PLoS Biology)
The importance of intratumour genetic and functional heterogeneity is increasingly recognised as a driver of cancer progression and survival outcome. Understanding how tumour clonal heterogeneity impacts upon therapeutic outcome, however, is still an area of unmet clinical and scientific need. TRACERx (TRAcking non-small cell lung Cancer Evolution through therapy [Rx]), a prospective study of patients with primary non-small cell lung cancer (NSCLC), aims to define the evolutionary trajectories of lung cancer in both space and time through multiregion and longitudinal tumour sampling and genetic analysis. By following cancers from diagnosis to relapse, tracking the evolutionary trajectories of tumours in relation to therapeutic interventions, and determining the impact of clonal heterogeneity on clinical outcomes, TRACERx may help to identify novel therapeutic targets for NSCLC and may also serve as a model applicable to other cancer types.